Protective role of complement factor H against the development of preeclampsia - Yasmin, Hadida; Agostinis, Chiara; Toffoli, Miriam; Roy, Tamali; Pegoraro, Silvia; Balduit, Andrea; Zito, Gabriella; Di Simone, Nicoletta; Ricci, Giuseppe; Madan, Taruna; Kishore, Uday; Bulla, Roberta (Frontiers in Immunology, 2024)
Pregnancy is an immunologically regulated, complex process where a tightly controlled complement system plays a crucial role in the successful establishment of pregnancy and parturition. Complement inhibitors at the feto-maternal interface are likely to prevent inappropriate complement activation to protect the fetus. In the present study, we aimed at understanding the role of Factor H (FH), as a negative regulator of complement activation, in normal pregnancy and in a model of pathological pregnancy, i.e. preeclampsia (PE). The distribution and expression of FH was investigated in placental tissues, different placental cells, and in sera of healthy (CTRL) or PE pregnant women via immunohistochemistry, RT-qPCR, ELISA, and Western blot. Our results showed a differential expression of FH among the placental cell types, decidual stromal cells (DSCs), decidual endothelial cells (DECs), and extravillous trophoblasts (EVTs). Interestingly, FH was found to be considerably less expressed in the placental tissues of PE patients compared to normal placental tissue both at mRNA and protein levels. Similar results were also obtained by measuring circulating FH levels in the sera of third trimester CTRL and PE mothers. Syncytiotrophoblast microvesicles, isolated from the placental tissues of PE and CTRL women downregulated FH expression by DECs. The present study suggests that FH is ubiquitously present in the placenta and plays a protective role during pregnancy.